2011
DOI: 10.1093/ageing/afr010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive impairment on the predictive value of multimorbidity for the increase in disability in the oldest old: the Leiden 85-plus Study

Abstract: Background: prevention of disability is an important aim of healthcare for older persons. Selection of persons at risk is a first crucial step in this process.Objectives: this study investigates the predictive value of multimorbidity for the development of disability in the general population of very old people and the role of cognitive impairment in this association.Design: the Leiden 85-plus Study (1997–2004) is an observational prospective cohort study with 5 years of follow-up.Setting: general population o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…Interestingly, in a previous analysis in the Leiden 85-plus Study, we found that chronic multimorbidity predicts an accelerated increase in ADL disability in very old persons with a good cognitive function [24]. This study shows that also an acute illness predicts an accelerated increase in ADL disability in the oldest-old without ADL disability at 86 years.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, in a previous analysis in the Leiden 85-plus Study, we found that chronic multimorbidity predicts an accelerated increase in ADL disability in very old persons with a good cognitive function [24]. This study shows that also an acute illness predicts an accelerated increase in ADL disability in the oldest-old without ADL disability at 86 years.…”
Section: Discussionsupporting
confidence: 58%
“…The biggest difficulties were reported with cutting nails and the smallest with eating meals. A study [22] conducted in the Netherlands on a group of 594 patients aged 85+ showed that in multi-disease patients the median value in the ADL scale amounted to 11 points, while Swedish research [23] revealed that in 51% of the persons studied aged 87-93 years, there was a decrease in ADL results within three years.…”
Section: Resultsmentioning
confidence: 96%
“…Drewes [22] used a 9-36 score in his study. Every activity could be scored in a four-point scale where 1 represents full independence and 4 full dependence.…”
Section: Discussionmentioning
confidence: 99%
“…20 In the longitudinal Leiden 85-plus Study (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004), the presence of two or more chronic conditions predicted accelerated ADL disability over time among individuals with normal cognitive function. 22 In addition, several studies have shown an association between multimorbidity and mortality across a range of conditions, [23][24][25][26] although this relationship is inconsistent and may be mediated by disability. 27,28 The quality of care for patients with multiple chronic conditions appears to vary based on both the number and types of conditions involved.…”
Section: Available Evidence and Data On Multimorbiditymentioning
confidence: 99%